2006
DOI: 10.1186/1471-2466-6-10
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, respiratory symptoms and likely asthma in young people: evidence from postal questionnaire surveys in the Wythenshawe Community Asthma Project (WYCAP)

Abstract: BackgroundAlthough it is recognised that smoking is a major risk factor for subjects with chronic obstructive pulmonary disease and is associated with respiratory symptoms, there is less agreement concerning the relationship between asthma and smoking. This study aims to examine the relationship between cigarette smoking and asthma prevalence.MethodData were used from two postal questionnaire surveys (1999 and 2001) in two general practice populations, using a respiratory questionnaire based on the ECRHQ and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Nevertheless, our estimates for well-known risk factors of asthma symptoms, such as smoking and a family history of asthma or atopy, are in the same range as those described in the literature. In a study among young adults, the odds ratio for asthma-like symptoms varied from 1.74 (shortness of breath) to 3 (wheezing) for smoking [28]. In a study conducted in Northern Europe, the odds ratio of presenting wheezing in the last 12 months ranged from 1.5-3.6 depending on the intensity of smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our estimates for well-known risk factors of asthma symptoms, such as smoking and a family history of asthma or atopy, are in the same range as those described in the literature. In a study among young adults, the odds ratio for asthma-like symptoms varied from 1.74 (shortness of breath) to 3 (wheezing) for smoking [28]. In a study conducted in Northern Europe, the odds ratio of presenting wheezing in the last 12 months ranged from 1.5-3.6 depending on the intensity of smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Data are scarce regarding airway pathology in asthmatic patients who smoke, and results from community studies provide inconsistent results [25]. Studies have shown that the combination of smoking and asthma negatively affect lung functionality and inflammation to a greater degree than either factor alone [1,5,19,24].…”
Section: Secondary Analysis-outcomesmentioning
confidence: 96%
“…There appeared to be an increased prevalence of asthma according to smoking and second-hand smoke exposure [8,9]. Among the factors was the major variable of exposure to smoking in childhood, which relates to direct and indirect smoking.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, about 1.9 million people die annually from these diseases. Recently, the effects of secondhand smoking on children and adolescents with asthma has attracted a great deal of research attention [8][9][10][11][12]. Asthma is more frequent in children and adolescents than adults, and it can be dangerous when asthma occurs in a susceptible group of people.…”
Section: Introductionmentioning
confidence: 99%